Broadband and Ultra-Low Threshold Optical Bistability in Guided-Mode Resonance Grating Nanostructures of Quasi-Bound States in the Continuum - Xin Li (MDPI AG, 2021)
We model optical bistability in all-dielectric guide-mode resonance grating (GMR) nanostructures working at quasi-bound states in the continuum (BICs). The complementary metal-oxide-semiconductor (CMOS) compatible material silicon nitride (SiN) is used for the design of nanostructures and simulations. The ultra-low threshold of input intensity in the feasible nanostructure for nanofabrication is obtained at the level of ~100 W/cm2 driven by quasi-BICs. Additionally, the resonance wavelength in the GMR nanostructure can be widely tuned by incident angles with the slightly changed Q-factor that enables the optical bistable devices to work efficiently over a wide spectrum. The impact of the defects of grating that may be introduced in the fabrication process on the optical properties is discussed, and the tolerance of the defects to the optical performance of the device is confirmed. The results indicate that the GMR nanostructures of broadband and ultra-low threshold optical bistability driven by quasi-BICs are promising in the application of all-optical devices.